Effects of Rifampin and Ketoconazole on Pharmacokinetics of Morinidazole in Healthy Chinese Subjects - Pang, Xiaoyan (American Society for Microbiology, 2014)
Morinidazole, a 5-nitroimidazole antimicrobial drug, has been approved for the treatment of amoebiasis, trichomoniasis, and anaerobic bacterial infections in China. It was reported that drug-drug interaction happened after the coadministration of ornidazole, an analog of morinidazole, and rifampin or ketoconazole. Therefore, we measured the plasma pharmacokinetics (PK) of morinidazole and its metabolites in the healthy Chinese volunteers prior to and following the administration of rifampin or ketoconazole using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The area under the concentration-time curve from time 0 to time t (AUC(0-t)) and maximum concentration in serum (C(max)) of morinidazole were decreased by 28% and 23%, respectively, after 6 days of exposure to 600 mg of rifampin once daily; the C(max)s of N(+)-glucuronides were increased by 14%, while their AUC(0-t)s were hardly changed. After 7 days of exposure to 200 mg of ketoconazole once daily, the AUC(0-t) and C(max) of the parent drug were not affected significantly. C(max)s of N(+)-glucuronides were decreased by 23%; AUC(0-t)s were decreased by 14%. The exposure of sulfate conjugate was hardly changed after the coadministration of rifampin or ketoconazole. Using recombinant enzyme of UGT1A9 and human hepatocytes, the mechanism of the altered PK behaviors of morinidazole and its metabolites was investigated. In human hepatocytes, ketoconazole dose dependently inhibited the formation of N(+)-glucuronides (50% inhibitory concentration [IC(50)], 1.5 μM), while rifampin induced the mRNA level of UGT1A9 by 28% and the activity of UGT1A9 by 53%. In conclusion, the effects of rifampin and ketoconazole on the plasma exposures of morinidazole and N(+)-glucuronide are less than 50%; therefore, rifampin and ketoconazole have little clinical significance in the pharmacokinetics of morinidazole.